Untangling the Rhizosphere Bacterial Community Composition and Response of Soil Physiochemical Properties to Different Nitrogen Applications in Sugarcane Field - Khan, Abdullah; Jiang, Hongtao; Bu, Junyao; Adnan, Muhammad; Gillani, Syeda Wajeeha; Hussain, Muhammad Azhar; Zhang, Muqing (Frontiers in Microbiology, 2022)
Minimizing the use of chemical fertilizers and investigating an appropriate ecofriendly level of nitrogen fertilizer is the key to sustainable agriculture. Sugarcane is the main cash crop of China, especially Guangxi region. Information regarding the effect of different nitrogen levels on sugarcane rhizosphere microbiota is still a few. In this study we evaluated the effect of four different levels of nitrogen fertilizers on rhizosphere bacterial composition, soil physiochemical properties and sugarcane agronomic and yield performance using high throughput sequencing. The four treatments combination were CK (no fertilizers), low (L,100 kg ha-1), medium (M,150 kg ha-1) and high (H,200 kg ha-1). The results showed that medium nitrogen application significantly altered the rhizosphere bacterial community, soil properties, and sugarcane yield. The richness and evenness of the bacterial community was observed to be more in M treatment than CK. Important bacterial phyla Acidobacteria and Proteobacteria increased by 47% and 71% in M treatment. At genus level Acidothermus and Bradyrhizobium increased by 77.2% and 30.3% in M treatment. Principal component analysis (PCA) and cluster analysis further confirmed the level of differences among the treatments. 80% of the variation among the treatments was explained by PCA. Spearmen correlation heatmap showed that environmental factors such as pH, AP, AK, and SCAT were the key factors impacting sugarcane rhizosphere microbiome composition. Though the high and low nitrogen application alters the bacterial community and plant performance but medium nitrogen application appears to be ecofriendly, productive and appropriate nitrogen application rate for the Guangxi region.